PENGARUH PEMBERIAN KURMA MUDA TERHADAP PERCEPATAN KALA I PERSALINAN DI TG BALAI KARIMUN - Handayani, Danika; Mona, Silvia; Juni Ekasari, Dian (Universitas Batam, 2025)
The progress of the labor process depends heavily on adequate uterine contractions. His or uterine contractions during the labor process are the result of a complex mechanism that occurs in the smooth muscles of the uterus. One of the contents of dates, namely tannins, serotonin, calcium, linoleic acid, plays an important role in the contraction of smooth muscles of the cervix. Dates also affect oxytocin receptors and make the uterine muscles respond better to oxytocin, thus strengthening contractions. The underlying mechanism of the influence of dates on estrogen and progesterone levels. A study reported that date extract was shown to increase estrogen and progesterone levels. So, dates are useful in maintaining energy and strengthening uterine muscles. Dates also help the uterus stretch and prepare the uterus for the fetus to pass through during the labor process. Quantitative research method with This type of research is pre-experiment design. The design of this study is a posttest only control group design. The purpose of the study was to determine the Effect of Giving Young Dates on the Acceleration of Period I Childbirth The results of the accelerated period I research obtained a p-value of 0.000 < 0.05, then H0 was rejected, so that there was a significant influence and difference that occurred in the first stage of childbirth between before being given young date therapy treatment and after being given treatment to pregnant women in Period I. Keywords: dates, labor, firststage